Studi Perbaikan Kualitas Tegangan Pada Jaringan Distribusi Primer 20 kV di Kota Gorontalo - James P. Ulahayanan; Lily S. Patras; Fielman Lisi (Universitas Sam Ratulangi, 2019)
Abstract – The purpose of this research is to analyse the quality of voltage improvements in 20kV's primary distribution network in Gorontalo City. The method used in this research is through library studies, field studies, discussion as well as analyzing the quality improvement of voltage in 20 kV primary distribution network in Gorontalo City, the best of IS3. Based on the results of the analysis based on the data calculated on IS3 the value of drop voltage far exceeds the standard of only 14650.136 volts. As for the standard voltage received is ± 10% of the nominal voltage where the nominal voltage is 20000 volt, if the voltage is received at the standard end of 18000 volts. Key words: Improvements in voltage quality , 20 kV Primary Distribution.Abstrak — Tujuan penelitian ini adalah untuk menganalisis perbaikan kualitas tegangan pada jaringan distribusi primer 20kV di kota Gorontalo. Metode yang digunakan dalam penelitian ini adalah melalui studi pustaka, studi lapangan, diskusi serta menganalisa perbaikan kualitas tegangan pada jaringan distribusi primer 20 kV di kota Gorontalo, kususnya pada penyulang IS3. Berdasarkan hasil analisis berdasarkan data yang dihitung pada IS3 didapati nilai tegangan drop jauh melebihi standar yaitu hanya 14650,136 volt. Sedangkan untuk standar tegangan yang diterima adalah 12Â±